Contact based void partitioning to assess filtration properties in DEM simulations. (March 2015) - O'Sullivan, C.; Bluthé, J.; Sejpar, K.; Shire, T.; Cheung, L.Y.G.
Abstract: Discrete element method (DEM) simulations model the behaviour of a granular material by explicitly considering the individual particles. In principle, DEM analyses then provide a means to relate particle scale mechanisms with the overall, macro-scale response. However, interpretative algorithms must be applied to gain useful scientific insight using the very large amount of data available from DEM simulations. The particle and contact coordinates as well as the contact orientations can be directly obtained from a DEM simulation and the application of measures such as the coordination number and the fabric tensor to describe these data is now well-established. However, a granular material has two phases and a full description of the material also requires consideration of the voids. Quantitative analysis of the void space can give further insight into directional fabric and is also useful in assessing the filtration characteristics of a granular material. The void topology is not directly given by the DEM simulation data; rather it must be inferred from the geometry of particle phase. The current study considers the use of the contact coordinates to partition the void space for 3D DEM simulation datasets and to define individual voids as well as the boundaries or constrictions between the voids. The measured constriction sizes are comparable to those calculated using Delaunay-triangulation based methods, and the contact-based method has the advantage of being less subjective. In an example application, the method was applied to DEM models of reservoir sandstones to establish the relationship between particle and constriction sizes as well as the relationship between the void topology and the coordination number and the evolution of these properties during shearing.